Chemical Control of broomrape (Orobanche crenata Forsk.) in Faba Bean (Vicia faba L.) in Northern Sudan (University of Khartoum Journal of Agricultural Sciences, 2023)
An experiment was conducted in a Faba bean plot infested withan Orobanche crenata sick plot, at Merowe Research Station farm, in theNorthern State, Sudan, for 3 consecutive seasons (2007/08 - 2009/10). Theobjectives of the experiment were to evaluate the herbicidal efficacy ofImazethapyr (Pursuit 10 E.C) on Orobanche crenata Forsk. and effect onfaba bean (Vicia faba L.) growth and yield. The results showed that fababean was tolerant to the herbicide. The herbicide, reduced the number andair-dry weight of O. crenata shoots by 12 - 83% and 17- 87%, respectively,and increased faba bean seed yield by 10-243%, in comparison to theOrobanche infested control. Imazethapyr at 0.075 kg a.i/ha applied 15 daysafter sowing (DAS) significantly reduced O. crenata emergence and dryweight, effected the highest faba bean yield, henceforth could be usedsafely to control O. crenata in faba bean.